Gadamer's Hermeneutic Analysis For Digital Illustration Barong & Rangda On Emba Jeans By Illustrator Monez - Ni Nyoman Sri Witari; I Wayan Swandi; I Wayan Setem; Alit Kumala Dewi (Warna Komunikasi, 2025)
Emba Jeans products promoted in the July 2023 season are rich in Balinese tradition, transforming the figures of Barong and Rangda as objects of creativity. The reproduction of the meaning of the text contained in the illustrations is very unique and rich with interpretations This study aims to describe relevant interpretations and understandings to explore the meaning and aesthetic value of Monez's digital illustrations that compose Barong and Rangda as the main characters on Emba Jeans products with the theme "Chatarsist,  Music Turns Tragedy into Rhapsody" using Gadamer's hermeneutic theory approach. This research is important considering that Emba uses elements of Balinese cultural symbols as a source of creativity. The research method uses a qualitative approach, which is descriptive interpretive, with the research object of the characters of Barong and Rangda in the illustrations of Emba Jeans which are analyzed with four conceptual variables according to Gadamer's hermeneutics, namely historical analysis, dialectical analysis, prejudice analysis, and linguistic analysis. The results of the interpretation of the meaning obtained from this illustration are that Barong and Rangda are considered as symbols of catharsis, which is reflected by the activities of meditating and playing musical instruments as a representation of a means of human psychological reflection that is able to change negative things into great joy and enthusiasm.